2014
DOI: 10.1039/c4dt01312c
|View full text |Cite
|
Sign up to set email alerts
|

Retention of single crystals of two Co(ii) complexes during chemical reactions and rearrangement

Abstract: Monomeric [Co(II)(hep-H)(H2O)4]SO4 [1]SO4 and [Co(II)(hep-H)2(H2O)2](NO3)2 [2](NO3)2 have been developed from 2-(2-hydroxyethyl)pyridine (hep-H) and CoSO4·7H2O/Co(NO3)2·6H2O, respectively, at 298 K. On exposure to heat (120 °C), the light orange single crystal of [1]SO4 transforms to a pink single crystal corresponding to the neutral sulfato bridged dimeric complex [(Co(II)(hep-H)(H2O)2(μ2-sulfato-O,O'))2](3). However, the orange single crystal of [2](NO3)2 transforms to the single crystal of monomeric [Co(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…X-ray diffraction (XRD) patterns of known references 88 , 89 were compared to experimental XRD datasets obtained for Co-rich solids and Sm-rich solids, showing agreement with CoSO 4 ·6H 2 O 88 and Sm 2 (SO 4 ) 3 ·8H 2 O 89 (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…X-ray diffraction (XRD) patterns of known references 88 , 89 were compared to experimental XRD datasets obtained for Co-rich solids and Sm-rich solids, showing agreement with CoSO 4 ·6H 2 O 88 and Sm 2 (SO 4 ) 3 ·8H 2 O 89 (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 66%
“…All data presented in this study are included in this published article, its Supplementary Information, and Supplementary Source Data file. Data presented in this study include previously reported results 73 – 75 , 81 , 88 , 89 . Source data are provided with this paper.…”
mentioning
confidence: 80%
“…Two Co‐based nanocomposites ( NC‐1 and NC‐2 ) were synthesized from single‐source molecular precursors (SSMPs) using wet‐chemical reduction method. We used our previously reported SSMPs, 1 and 2 for synthesizing nanocomposites . The structure of 1 and 2 was found to be differ only by their counter anions (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“… (A‐B) Single‐source molecular precursors ( 1 and 2 )and synthesis of nanocomposites ( NC‐1 and NC‐2 ).…”
Section: Resultsmentioning
confidence: 99%
“…1. The structure displayed strong intermolecular hydrogen bonding between O1 of one molecule and N2 of other molecule establishing a closed circle structure to form dimeric arrangement [22]. Hirshfeld interactions studies: The interactions are further studied by Hirshfeld interactions studies.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%